CONSUMER DECISION MAKING IN SELECTING LAPTOP USING ANALYTICAL HIERARCHY PROCESS (AHP) METHOD (STUDY: HP, ASUS AND TOSHIBA) - Tampi, Yeriko A. N.; Pangemanan, Sifrid S.; Tumewu, Ferdinand J. (Jurnal EMBA : Jurnal Riset Ekonomi, Manajemen, Bisnis dan Akuntansi, 2016)
Developing laptop brings revolution in people daily life, it increases people standard of living and has great effect on business, science, education, medical sector, transportation and so on. This research used Analytical Hierarchy Process (AHP) to compare each laptop based on the criteria; value added features, peripheral specifications, core technical features, physical appearance and price and payment conditions. The respondent is 50 people and this research using purposive sampling. The respondent of this research is the people that have an experience used that three laptop. The result shows that Peripheral Specification is the most important criteria, followed by Core Technical Features factor, Value Added Features factor, followed with Price and Payment Condition and the last Physical Appearance factor. As the result, there are two from five criteria that influence the consumer to choose laptop. Peripheral Specification is the most preferred criteria compare with the others. Core Technical Features is in second position as the most preferred criteria chose by respondent. In best laptop result, HP become the best laptop chose by respondent, followed by ASUS and TOSHIBA chose by consumer that have an experience used that three laptop. Â  Keywords: customer decision making, AHP